2002
DOI: 10.1046/j.1365-2133.2002.05039.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of febrile ulceronecrotic Mucha-Habermann disease requiring debridement of necrotic skin and epidermal autograft

Abstract: We report a case of febrile ulceronecrotic Mucha-Habermann disease (FUMHD) in a 21-year-old man. This disease is a severe form of pityriasis lichenoides et varioliformis acuta (PLEVA) and is characterized by the sudden onset of diffuse ulcerations associated with high fever and systemic symptoms. It is sometimes lethal especially in elderly patients. In the present case, intense generalized maculopapular erythematous plaques with central necrosis developed progressively in association with a high fever. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 20 publications
(32 reference statements)
3
49
0
2
Order By: Relevance
“…Yanaba et al [23] observed a predominantly CD8+ lymphocytes infiltrate around the dermis and epidermis which might suggest a cytotoxic attack of lymphocytes to altered epidermal antigens.Some authors have suggested that PLEVA is a benign clonal disorder of activated T cell lymphocytes. Dereure et al [46] demonstrated that 13 of 20 (65%) PLEVA biopsy specimens had a dominant T cell clone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yanaba et al [23] observed a predominantly CD8+ lymphocytes infiltrate around the dermis and epidermis which might suggest a cytotoxic attack of lymphocytes to altered epidermal antigens.Some authors have suggested that PLEVA is a benign clonal disorder of activated T cell lymphocytes. Dereure et al [46] demonstrated that 13 of 20 (65%) PLEVA biopsy specimens had a dominant T cell clone.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive monotherapy with methotrexate [6,8,11,13,15,19,25,28,29,36,40] or cyclosporine [31,35] or a combination of one of these with a high dose of glucocorticoids [6,8,11,13,25,28,29,36,41,43] has been used in -several cases. Antibiotics like erythro-mycin, acyclovir, ultraviolet photother-apy (PUVA) [11,19], IVIG [5,28,36,41,] photochemotherapy [41], 4,4-diaminodiphenyl sulfone [7,8,10,23,] and debridement with skin grafting [23] have also been used to treat FUMHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diese seltene Dermatose gehört in die Gruppe der erythematosquamösen Erkrankungen und tritt pleomorph auf: papulosquamöse, hämorrhagisch-vesikulöse, papulonekrotische und selten ulzeronekrotische Verläufe wurden beschrieben [10,12]. Das Manifestationsalter liegt in den ersten Lebensdekaden [10].…”
Section: Kommentarunclassified